China's COVID-19 Control Strategy and Its Impact on the Global Pandemic - Ding, Difeng; Zhang, Ruilian (Frontiers in Public Health, 2022)
Public health crises are challenging for governments and health systems. Coronavirus disease 2019 (COVID-19) has presented huge challenges to humans worldwide. In the context of COVID-19 in China, we explore China’s control strategies and challenges. Accordingly, we identify the causes of those challenges, including social and natural factors, and the controls put in place. We contend that China’s control strategies slowed the spread of the global pandemic and that the Chinese vaccines have promoted global vaccine equity.